2018
DOI: 10.1108/ejtd-08-2018-0086
|View full text |Cite
|
Sign up to set email alerts
|

Team building, employee empowerment and employee competencies

Abstract: Purpose The purpose of this paper is to examine the impact of team building and employee empowerment on employee competencies and examine the moderating role of organizational learning culture in between these relationships. Design/methodology/approach An integrated research model is developed by combining resource-based view, signalling theory and experiential learning theory. The validity of the model is tested by applying moderated structural equation modelling (MSEM) approach to the data collected from 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(54 citation statements)
references
References 89 publications
(115 reference statements)
0
53
0
1
Order By: Relevance
“…Hence, the organization obtains improvements in the quality of its products, coordination of internal processes, customer satisfaction, the ability to adapt to changing market, brand image of the company and its products. On the other hand, Hooi and Ngui (2014) and Potnuru et al (2019) found that the learning capacity of small and medium enterprises mediates the effect of human resource practices on the performance. Other authors point out that "the organizational learning constitutes a cumulative set of knowledge over time, however, in small enterprises with up to 49 employees, there might not have structured processes of organizational learning, and therefore they propose that the organizational learning will have a negative and significant relationship with the organizational performance, they confirm the hypothesis (Vasconcelos et al, 2016).…”
Section: The Relationship Of Learning Orientation With Organizationalmentioning
confidence: 99%
“…Hence, the organization obtains improvements in the quality of its products, coordination of internal processes, customer satisfaction, the ability to adapt to changing market, brand image of the company and its products. On the other hand, Hooi and Ngui (2014) and Potnuru et al (2019) found that the learning capacity of small and medium enterprises mediates the effect of human resource practices on the performance. Other authors point out that "the organizational learning constitutes a cumulative set of knowledge over time, however, in small enterprises with up to 49 employees, there might not have structured processes of organizational learning, and therefore they propose that the organizational learning will have a negative and significant relationship with the organizational performance, they confirm the hypothesis (Vasconcelos et al, 2016).…”
Section: The Relationship Of Learning Orientation With Organizationalmentioning
confidence: 99%
“…Originating implemented predominantly in the case of athletic teams [13], team building practices have made their way throughout the years across a variety of occupational fields such as: software development [18] [19] [11], business [20], health care [21] [22], R&D Startups [5], education [10] [23] [24] and construction [25].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Although generally considered to be a yielder of good results [18] [25] team building does have some pitfalls, but as observed from previous practice most of these "wounds" are self-inflicted by the managerial team [27] as shown in Figure 1 [28]. Fig.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The literature explains the empowerment approach as a management concept that constructs on dimensions of intrinsic motivation, job design, participative decision making, social learning theory, and self-management (Alazzaz & Whyte, 2015). Potnuru, Sahoo, & Sharma (2019), associate these dimensions with the organization's knowledge sharing, rewards systems that could empower the employees to enhance organizational competitiveness and performance.…”
Section: Empowerment Approach and Employee Performancementioning
confidence: 99%